Shape-Up Shortcuts : Score a Hotter, Healthier Body in Half the Time! - Ator, Jen (New York Rodale Inc, 2013)
Most women have enough "to-do's" on their list, and trying to be perfect about exercise and healthy eating isn't the answer to a rocking body. This collection of fitness and diet tips includes targeted routines that maximize efficiency to get readers in and out of the gym - and into their tiniest bikinis.
Keywords: Reducing diets -- Reducing exercises -- Women--Health and hygiene